Metabolic syndrome and insulin resistance in Division 1 collegiate football players - Borchers, J. R.; Clem, K. L.; Habash, D. L.; Nagaraja, H. N.; Stockley, L. M.; Best, T. M. (Medicine & Science in Sports & Exercise, 2009)
Purpose: To estimate the prevalence of metabolic syndrome and insulin resistance in a cohort of Division 1 collegiate football players.